The Effect Of Mc Kenzie Exercise And Neck Stabilization Exercise On Neck Pain On Garments - Isidorus Jehaman; Suparno .; Redi Tantangan; Fitri Ramadhani Harahap (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
In doing sewing work, a tailor will arrange the work-place and the table into the most comfortable position which is sometimes a bit low and will cause the back to bend slightly and automatically the shoulders will be lifted to feel comfortable in sewing activities. A sedentary and monotonous position will burden the neck, shoulders, arms so that fatigue / discomfort / pain in the neck and upper-back area often occurs. Neck pain is pain is felt at the top of the spine. This is a sign that the joints, muscles or other parts of the neck are injured, strained or not functioning as they should. Neck pain is also a common problem. Two out of three people will experience it in their lifetime. To determine the difference between Mc Kenzie Exercise and Neck Stabilization Exercise Interventions on reducing neck pain in tailors at Bangko Lereng Market who came to Suparno's Independent Physiotherapy Practice. This research design uses a quasi-experimental method with a pre-test and post-test two group design using a purposive sampling technique. The population in this study were 25 employees and the samples were taken from 20 employees, who tailor garments at the Lereng market with neck pain. there is an impact of Mc Kenzie Exercise on reducing neck pain. There is an impact of Neck Stabilization Exercise on reducing neck pain there is no difference between Mc Kenzie Exercise intervention and the provision of Neck Stabilization Exercise in reducing neck pain. there is an effect of giving Mc Kenzie Exercise and Neck Stabilization Exercise interventions in reducing neck pain, but there is no difference in the intervention between those two. It is hoped that the sample can perform the movements that have been taught by the researcher independently in order to reduce neck pain